2018
DOI: 10.1021/acssynbio.8b00070
|View full text |Cite
|
Sign up to set email alerts
|

Combinatory Biosynthesis of Prenylated 4-Hydroxybenzoate Derivatives by Overexpression of the Substrate-Promiscuous Prenyltransferase XimB in Engineered E. coli

Abstract: Prenylated aromatic compounds are important intermediates in the biosynthesis of bioactive molecules such as 3-chromanols from plants, ubiquinones from prokaryotes and meroterpenoids from sponges. Biosynthesis of prenylated aromatic compounds using prokaryotic microorganisms has attracted increasing attention in the field of synthetic biology. In this study, we demonstrated that the production of 3-geranyl-4-hydroxybenzoic acid (GBA) and a variety of GBA analogues was feasible in a metabolically engineered E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…In a recent publication, we demonstrated that xiamenmycin B, an intermediate precursor of xiamenmycin A and one that does not incorporate threonine into the benzopyran core skeleton, could be synthesized in E. coli . [31]. Whether the surrogate E. coli host is more adaptable to the acetyl-CoA and NADPH stress than the natural Streptomyces host merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, we demonstrated that xiamenmycin B, an intermediate precursor of xiamenmycin A and one that does not incorporate threonine into the benzopyran core skeleton, could be synthesized in E. coli . [31]. Whether the surrogate E. coli host is more adaptable to the acetyl-CoA and NADPH stress than the natural Streptomyces host merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Xiamenmycin B was detected with a product yield of 90.7 mg/L (Figure A, Table ). Given that XimB catalyzes the formation of prenylated products ( 1 , 2 , 3 , 4 , 5 , and 6 ) (Figure S2) from 4-hydroxybenzoic acid analogues, six 4-hydroxybenzoic acid analogues ( 7 , 8 , 9 , 10 , 11 , and 12 ) (Table , Figure S3) were separately fed at a final concentration of 100 mg/L into the 24 h old cultures of strain XL01. Benzopyran products 13 and 14 were detected by feeding 7 and 8 , respectively, as confirmed by UPLC-QTOF-MS, and their yields were 48.9 and 27.7 mg/L, respectively (Figure A, S4, S5, and Table ).…”
Section: Resultsmentioning
confidence: 89%
“…Angular FC (20) and PC (21) were also detected when feeding the corresponding precursor, C8prenylated umbelliferone (18) (Figure 5D), and the titer of 21 reached 0.44 mg/L. We tried to coexpress the prenyltransferases, i.e., PcPT and PT2, with ximD and ximE in E. coli to directly use an easily accessible and cheap substrate, umbelliferone (16) ximD-ximE2 were then transformed into E. coli Rosetta (DE3) strain R-MVA containing pCDF-Duet-1-mvaE-mvaS-ERG8-EGR12-MVD1-idi, 29 respectively, generating two strains, XL10 and XL11. Umbelliferone ( 16) was fed to each strain at a final concentration of 100 mg/L.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility was corroborated with the detection of 3 when A. oryzae NSAR1 was cultured with 2 (see Figure S5A). Until now, several UbiA-type 4-hydroxybenzoate prenyltransferases from prokaryotes and eukaryotes have been identified, and usually show broad tolerance to the isoprenoid substrate, [14] whereas BisJ, as well as XimB, [15] is the few examples that are able to accept dimethylallyl pyrophosphate (DMAPP) as the prenyl donor.…”
mentioning
confidence: 99%